Orbicularis oris musculomucosal flap for anterior palatal fistula - Tiwari, V. K.; Sujata, Sarabahi (Indian Journal of Plastic Surgery, 2006)
Anterior palatal fistulae or residual anterior clefts are a frequent problem following palatoplasty. Various techniques have been used to repair such fistulae, each having its own advantages and disadvantages. We have successfully used orbicularis oris musculomucosal flap to close anterior fistula and residual clefts in 25 patients. This study shows the superiority of this flap over other techniques because of its reliable blood supply, easy elevation and transfer to fistula site and finally because it is a single-stage procedure.
Keywords: Labiobuccal sulcus; musculomucosal flap; palatal fistula